SYNERGIZING FORMAL AND SELF-REGULATED DIGITAL PRACTICES IN ISLAMIC SECONDARY EDUCATION: A MIXED-METHODS PREDICTIVE MODEL OF EFL LEARNERS’ SPEAKING PROFICIENCY - Sari Wulandari; Dias Andris; Listyaning Sumardiyani (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
In an era when digital ecosystems increasingly shape how learners think and communicate, understanding how such environments support second-language speaking development has become an academic and pedagogical imperative. This study examines how the synergy between Formal Digital Practice (FDP) and Self-Regulated Digital Practice (SRDP) contributes to EFL learners’ speaking proficiency, particularly within Islamic secondary education, where digital literacy is expected to align with values of discipline, responsibility, and adab (proper conduct). Using an explanatory sequential mixed-methods design, the study integrates pre–post speaking assessments, SRDP questionnaires, digital activity logs, and a Synergy Index with qualitative interviews to explore learners’ perceptions and strategic behaviors. Findings show significant gains in fluency, accuracy, and complexity, with a large effect size and strong predictive power of the Synergy Index, indicating that strategic integration rather than mere frequency of technology use drives linguistic improvement. Results further reveal that teacher modeling rooted in Islamic educational values and peer collaboration grounded in communal ethics enhance the effectiveness of integrated digital practices. The study concludes that meaningful speaking development emerges when formal and self-regulated digital practices operate coherently and reinforce one another. These findings validate the Integrated Digital Practice (IDP) Model and offer important implications for EFL curriculum design in Islamic-based schools, promoting sustained, autonomous, and ethically grounded oral communication.